2008
DOI: 10.1111/j.1537-2995.2008.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory testing of hepatitis C virus–positive enzyme immunoassay results in limited‐resource countries: should it be attempted?

Abstract: ABBREVIATIONS: CIA = chemiluminescence assay; S/C = signal-to-cutoff (ratio).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In the study performed by the CDC, in three different population arms whose HCV prevalence was either low (2%), medium (9·5%) or high (25%), it was demonstrated that when the S/CO ratio of a repeat reactive sample was ≥3·8, the true positivity rate with the confirmatory test was 95% (when tested with Abbott second generation EIA and Ortho third generation ELISA). In a similar study performed in China, it was stated that true positivity rate with the use of RIBA or NAT was 96·1% for EIA samples whose S/CO ratio was ≥3·8 with Ortho third generation EIA (Nelson & Shan, 2008). In another study correlation was also noticed with high false‐positive rates for sample S/CO ratios below the value of 3·8 (Contreras et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by the CDC, in three different population arms whose HCV prevalence was either low (2%), medium (9·5%) or high (25%), it was demonstrated that when the S/CO ratio of a repeat reactive sample was ≥3·8, the true positivity rate with the confirmatory test was 95% (when tested with Abbott second generation EIA and Ortho third generation ELISA). In a similar study performed in China, it was stated that true positivity rate with the use of RIBA or NAT was 96·1% for EIA samples whose S/CO ratio was ≥3·8 with Ortho third generation EIA (Nelson & Shan, 2008). In another study correlation was also noticed with high false‐positive rates for sample S/CO ratios below the value of 3·8 (Contreras et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have shown that relatively high sample‐to‐cutoff (s/co) ratios on screening immunoassays (IAs) for antibodies to hepatitis C virus (anti‐HCV) are predictive of confirmed‐positive results in both blood donor 1‐8 and nondonor populations 9‐16 . As well, it has been suggested that an anti‐HCV status can be assigned solely on the basis of screening IA s/co ratios 17,18 . The purpose of this study was to compare the s/co ratio distributions of biologic false‐reactive (BFR) with confirmed‐positive results for four chemiluminescent immunoassays (ChLIAs) in a blood donor population.…”
mentioning
confidence: 99%
“…HBV DNA level measured using poly merase chain reaction (PCR) is a good diagnostic assay for the diagnosis of HBV, however, due to its high cost in many countries and regions, especially low-income countries, ELISA is still used without further confirming viral titer with PCR. Significantly, many HBeAg (−) patients show chronic active HBV in further screening by PCR and vice versa (Nelson and Shan 2008). Therefore, it is important to identify new reliable serum markers as indicators of the active status of HBeAg (−) CHB.…”
Section: Introductionmentioning
confidence: 99%